The supraduodenal pedicle can be a useful landmark of the common bile duct in laparoscopic cholecystectomy - Lei Wang; Hui Hou (Videosurgery and Other Miniinvasive Techniques)
This investigation was undertaken to determine whether the supraduodenal pedicle (SP) can assist in defining the location of the common bile duct (CBD) during laparoscopic cholecystectomy (LC). The supraduodenal pedicle was recognizable in 100/122 (82%) consecutive patients undergoing LC in this hospital. The SP displayed either thin (9/100, 9%) or obvious thick vessels (91/100, 91%), 38/100 (38%) cases showed a single branch vessel and 62/100 (62%) cases showed two or more branches. The CBD and SP were both present in 68/100 (68%) patients. The right most branch of the SP ran along the ventral (40/68, 58.8%) or the left edge (28/68, 41.2%) of the CBD. In 32 cases with an invisible CBD but a visible SP, the CBD was successfully found close to the right most branch of the SP in all patients after slightly separating them. The SP can be a useful landmark to quickly and accurately locate the CBD in LC.